2011
DOI: 10.1177/1043454211409585
|View full text |Cite
|
Sign up to set email alerts
|

Education Given to Parents of Children Newly Diagnosed With Acute Lymphoblastic Leukemia

Abstract: Over the past 30 years, diagnosis and treatment of childhood cancers has developed significantly due to medical research and advancements in technology. As a result, prognosis has improved, and approximately 80% of children diagnosed with cancer survive into adulthood. Care has also shifted from a sole inpatient setting to include outpatient treatment where possible, and both these trends have resulted in a shift in the focus of research to the psychosocial and psychological effects of treatment on children an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
116
0
15

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(135 citation statements)
references
References 25 publications
4
116
0
15
Order By: Relevance
“…Therefore, it may be a relevant tailored intervention to help improve communication during medical visits, according to specific demands of parents and children, which is in agreement with literature (Aburn & Gott, 2011;Coyne & Gallagher, 2011;Coyne & Harder, 2011;Howells & Lopez, 2008;Lambert et al, 2011;Ringnér et al, 2010;Zwaanswijk et al, 2011).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Therefore, it may be a relevant tailored intervention to help improve communication during medical visits, according to specific demands of parents and children, which is in agreement with literature (Aburn & Gott, 2011;Coyne & Gallagher, 2011;Coyne & Harder, 2011;Howells & Lopez, 2008;Lambert et al, 2011;Ringnér et al, 2010;Zwaanswijk et al, 2011).…”
Section: Discussionsupporting
confidence: 74%
“…Another relevant aspect highlighted by the literature are the individual preferences for the kind and amount of information, which is related to the adaptation to treatment and satisfaction with health services, endorsing the need for tailored interventions that may contribute to the development of better interactions between pediatricians, caregivers, and children (Aburn & Gott, 2011;Coyne & Gallagher, 2011;Coyne & Harder, 2011;Howells & Lopez, 2008;Lambert, Glacken, & McCarron, 2011;Ringnér, Jansson, & Graneheim, 2010;Zwaanswijk et al, 2011). Therefore, psychosocial interventions are important in order to understand the triadic interaction and provide better communication in pediatric settings.…”
mentioning
confidence: 99%
“…The diagnosis of an illness like cancer must be followed by parents' preparation to the care of a child that demands precise and complex care. A well-planned discharge education, home visits, and telephone follow-up are some of the possible interventions to prepare these families (Aburn, Gott 2011;Sari et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Parents need to receive information about the illness progression and treatment responses continuously. A good relationship with the medical team is an essential resource for these families, increasing safety during the care at home (Sari, 2013;Aburn, 2011).…”
Section: The Transition Between Hospital and Homementioning
confidence: 99%
“…Patenaude and Kupst [9] reviewed research on psychosocial paediatric oncology research, and found that in the past 30 years paediatric oncology care has gone through changes from avoidance of communication about cancer to an emphasis on straightforward discussion of the illness and prognosis. Research has shown the benefits of information/education for children and adolescents [25][26], and for parents [27].…”
Section: Introductionmentioning
confidence: 99%